Acceso a semillas en Senegal: Un análisis etnográfico y de redes sociales con enfoque de género - Anna Porcuna-Ferrer; Quintero, Diana K; Howland, Fanny (2025)
English Seed Access in Senegal: An Ethnographic and Social Network Analysis with a Gender Lens This research examines how historical, social, and gender dynamics shape access to seeds in a Basari community in southeastern Senegal. Based on 18 months of ethnographic fieldwork (2020–2021), it combines access theory, social network analysis, and feminist political ecology. Findings trace three key phases: the peanut boom (1900–1960), its crisis (1960–2000), and the post-2000 shift to cereals driven by food security policies. Analysis of six crops reveals distinct circulation logics: peanuts through markets and projects, sorghum via kinship ties, and Bambara groundnut among women in solidarity networks. Gender and intersectionality prove central: women are increasingly crucial in sorghum management, play pivotal roles in Bambara networks, yet face limited access to project-introduced rice. Overall, the study shows how new crops and external interventions reshape social ties and deepen inequalities, underscoring that resilience in small-scale farming must be understood as relational, political, and historically embedded.